Pengolahan Sagu menjadi mie prebiotik sebagai makanan fungsional dan upaya peningkatan ketahanan pangan di Desa Alai Selatan, Kecamatan Tebing Tinggi Barat, Kepulauan Meranti - Atria Martina; Wahyu Lestari; Tetty Marta Linda; Saberina Hasibuan; Imelda Wardani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Noodles are a processed food product favored by most Indonesians, generally made from wheat which must be imported. Kepulauan Meranti Regency is the largest producer of sago in Indonesia. One of the products made from sago that is widely produced in Meranti is sa.go noodle. Making noodles with local raw materials such as sago and sweet potato is an effort to improve food security. Traditional sago noodle has high carbohydrate and fiber content but still has disadvantages such as not having inulin content as a prebiotic, less antioxidant and a less attractive color, while purple sweet potato contains inulin as prebiotic components, high antioxidants, vitamins and minerals.The utilization of prebiotics insago noodle has multiple advantages since they improved probiotic growth in the body, sensory features and provide a more well-balanced nutritional composition as functional food. This community service program aims to training on the process of making prebiotic sago noodles to the community in Alai Selatan Village.This activities are carried out by course and practice methods.The results showed that the participants were interested in making prebiotic sago noodles because they had a more attractive features, more nutritious and had a delicious taste. Prebiotic sago noodles can be used as an effort to biodiversify sago noodle products to support food security and improve the community's economy.